Monetary Policy and Macroeconomic Stability in Latin America The Cases of Brazil, Chile, Colombia and Mexico - de Mello, Luiz (OECD Economics Department Working Papers, 2007)
In 1999, new monetary policy regimes were adopted in Brazil, Chile, Colombia and Mexico, combining inflation targeting with floating exchange rates. These regime changes have been accompanied by lower volatility in the monetary stance in Brazil, Colombia and Mexico, despite higher inflation volatility in Brazil and Colombia. This paper estimates a conventional New Keynesian model for these four countries and shows that: i) the post-1999 regime has been associated with greater responsiveness by the monetary authority to changes in expected inflation in Brazil and Chile, while in Colombia and Mexico monetary policy has become less counter-cyclical, ii) lower interest-rate volatility in the post-1999 period owes more to a benign economic environment than to a change in the policy setting, and iii) the change in the monetary regime has not yet resulted in a reduction in output volatility in these countries